(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2024)
he research objectives were to identify the role of Al-Baath University in spreading the culture of entrepreneurship in light of the entrepreneurial university, in addition to identifying the differences between the average grades of the research sample according to the college variable. The descriptive analytical approach was adopted, and the questionnaire was a tool for collecting data. The research sample consisted of (100 ) of administrators in the faculties of Al-Baath University, and the following results were reached: The degree to which Al-Baath University played its role in spreading the culture of entrepreneurship was weak. The criterion of strategic alliances with external stakeholders ranked first with a moderate degree, then the criterion for evaluating entrepreneurial practices ranked second with a moderate degree, while in third place came the criterion of vision and mission. The entrepreneurial strategy has a moderate degree, followed in fourth place by the university support criterion with a weak degree, then in fifth place is the criterion for entrepreneurial education based on creativity and innovation with a weak degree, then in sixth place is the standard of internationalization and external university relations with a weak degree, and the last place was for the resources and infrastructure criterion with a weak degree. Weak. - There is no differences statistically at the significance level of 0.05 between the averages of the research sample’s answers at the criterion (vision, mission, and entrepreneurial strategy, entrepreneurial education based on creativity and innovation, university support) according to the college variable. There are differences statistically at the significance level of 0.05 between the averages of the research sample’s answers to the criteria (resources and infrastructure, strategic alliances with external stakeholders (community partnership), internationalization and external university relations, evaluation of entrepreneurial practices) according to the college variable, in favor of applied colleges.